Evaluation of End-Products in Architecture Design Process: A Fuzzy Decision-Making Model - Palabiyik, Serkan; Colakoglu, Birgul (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2012)
This paper presents a study on the development of a fuzzy multi-criteria decision-making model for the evaluation of end products of the architectural design process. Potentials of the developed model were investigated within the scope of architectural design education, specifically an international design studio titled Design for Disassembly and Reuse: Design & Building Multipurpose Transformable Pavilions. The studio work followed a design process that integrated systematic and heuristic thinking. The design objectives and assessment criteria were clearly set out at the beginning of the process by the studio coordinator with the aim of narrowing the design space and increasing awareness of the consequences of design decisions. At the end of the design process, designs produced in the studio were evaluated using the developed model to support decision making. The model facilitated the identification of positive and negative aspects of the designs and selection of the design alternative that best met the studio objectives set at the beginning.
Keywords: AHP; fuzzy logic; decision making model; evaluation of architectural designs; Architecture